Modelling alkali metal emissions in large-eddy simulation of a preheated pulverised-coal turbulent jet flame using tabulated chemistry. Issue 2 (4th March 2018) - Wan, Kaidi; Xia, Jun; Vervisch, Luc; Liu, Yingzu; Wang, Zhihua; Cen, Kefa
Abstract : The numerical modelling of alkali metal reacting dynamics in turbulent pulverised-coal combustion is discussed using tabulated sodium chemistry in large eddy simulation (LES). A lookup table is constructed from a detailed sodium chemistry mechanism including five sodium species, i.e. Na, NaO, NaO2, NaOH and Na2 O2 H2, and 24 elementary reactions. This sodium chemistry table contains four coordinates, i.e. the equivalence ratio, the mass fraction of the sodium element, the gas-phase temperature, and a progress variable. The table is first validated against the detailed sodium chemistry mechanism by zero-dimensional simulations. Then, LES of a turbulent pulverised-coal jet flame is performed and major coal-flame parameters compared against experiments. The chemical percolation devolatilisation (CPD) model and the partially stirred reactor (PaSR) model are employed to predict coal pyrolysis and gas-phase combustion, respectively. The response of the five sodium species in the pulverised-coal jet flame is subsequently examined. Finally, a systematic global sensitivity analysis of the sodium lookup table is performed and the accuracy of the proposed tabulated sodium chemistry approach has been calibrated.